A review on the Hire Purchase (Amendment) Act 2010 / Nur 'Ain Nadira Ramli …[et al.] - Ramli, Nur 'Ain Nadira; Zolkaflee, Nabilah Nasuha; Mohd Yusof, Nurul Adibah Afnan; Che Ani @ Che Azmi, Noorharumi (2013)
The objective of choosing hire purchase field in completing the project paper is to find the effectiveness of the amended act in guiding the hire purchase transaction between hirers and dealers. The last hire purchase act was discovered with many problem and loopholes where the amended act tries to fill in. Thus, the researchers want to observe the effectiveness of the Act through Article 30A and 31 of the Act. The method used by the researchers is by empirical research through conducting interviews with several respondents. The questions conducted are on the applications of the provision and the effect it gave to the hirers and the dealers. The researchers found that both articles are good in application but still need to be review in order to ensure the right, obligation and liability between hirers and dealers are balanced. The researchers recommends to alter section 30A where the idea of the booking fees should be remained; the consumer shall be maintained their right of cancellation, and increasing the sanction by revoking the car dealers' license in dealing with cars if caught commits fraudulent activities towards the consumers.